2021
DOI: 10.12703/r/10-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-obstructive azoospermia: current and future perspectives

Abstract: Infertility affects 1 in 6 couples, and male factor infertility has been implicated as a cause in 50% of cases. Azoospermia is defined as the absence of spermatozoa in the ejaculate and is considered the most extreme form of male factor infertility. Historically, these men were considered sterile but, with the advent of testicular sperm extraction and assisted reproductive technologies, men with azoospermia are able to biologically father their own children. Non-obstructive azoospermia (NOA) occurs when there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The basic common function of all WD40-repeat proteins is to coordinate the assembly of multi-protein complex, where the repeating units act as a rigid scaffolds for protein interactions 22 . The complex structure of sperm flagella contained a series of WD40-domain-containing proteins 1 , 23 . These proteins including CFAP43 (also known as WDR96 , MIM: 617558), CFAP44 (also known as WDR52 , MIM: 617559) and WDR66 (MIM: 618146) are associated with MMAF and their bi-allelic variants can reduce sperm motility and cause male infertility 24 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The basic common function of all WD40-repeat proteins is to coordinate the assembly of multi-protein complex, where the repeating units act as a rigid scaffolds for protein interactions 22 . The complex structure of sperm flagella contained a series of WD40-domain-containing proteins 1 , 23 . These proteins including CFAP43 (also known as WDR96 , MIM: 617558), CFAP44 (also known as WDR52 , MIM: 617559) and WDR66 (MIM: 618146) are associated with MMAF and their bi-allelic variants can reduce sperm motility and cause male infertility 24 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason for the lack of a statistically signi cant difference in T/E2 between successful and unsuccessful sperm retrieval by micro TESE is unknown. So far, various clinical and hormone parameters have been investigated as potential predictors of successful sperm retrieval but the evidence for clinical and biochemical markers is con icting 19 . One study found that a decreased seminal testosterone/estradiol ratio could be a good indicator for identifying absence of sperm production in NOA patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Men with NOA must undergo surgical sperm retrieval and intracytoplasmic sperm injection in order to father biological children, and the live birth rate is ~25% [ 32 ]. Artificial intelligence and predictive modelling may aid in increasing the sperm retrieval rate in men with NOA [ 33 ]. Additionally, several promising experimental techniques to restore fertility in men with NOA are currently in the research ‘pipeline’, including transplantation of spermatogonial stem cells, differentiation of adult or embryonic stem cells, and gene therapy [ 34 ].…”
Section: Future Perspectives In Azoospermiamentioning
confidence: 99%